Histone H4 methyltransferase Suv420h2 maintains fidelity of osteoblast differentiation - Farzaneh, Khani (J Cell Biochem, 2016)
Osteogenic lineage commitment and progression is controlled by multiple signaling pathways (e.g., WNT, BMP, FGF) that converge on bone-related transcription factors. Access of osteogenic transcription factors to chromatin is controlled by epigenetic regulators that generate post-translational modifications of histones (‘histone code’), as well as read, edit and/or erase these modifications. Our understanding of the biological role of epigenetic regulators in osteoblast differentiation remains limited. Therefore, we performed next-generation RNA sequencing (RNA-seq) and established which chromatin-related proteins are robustly expressed in mouse bone tissues (e.g., fracture callus, calvarial bone). These studies also revealed that cells with increased osteogenic potential have higher levels of the H4K20 methyl transferase Suv420h2 compared to other methyl transferases (e.g., Suv39h1, Suv39h2, Suv420h1, Ezh1, Ezh2). We find that all six epigenetic regulators are transiently expressed at different stages of osteoblast differentiation in culture, with maximal mRNAs levels of Suv39h1 and Suv39h2 (at day 3) preceding maximal expression of Suv420h1 and Suv420h2 (at day 7) and developmental stages that reflect, respectively, early and later collagen matrix deposition. Loss of function analysis of Suv420h2 by siRNA depletion shows loss of H4K20 methylation and decreased expression of bone biomarkers (e.g., alkaline phosphatase/Alpl) and osteogenic transcription factors (e.g., Sp7/Osterix). Furthermore, Suv420h2 is required for matrix mineralization during osteoblast differentiation. We conclude that Suv420h2 controls the H4K20 methylome of osteoblasts and is critical for normal progression of osteoblastogenesis.